The Nature and Layers of Dynamic Capabilities of Firms Engaging in Business Model Innovations: A Qualitative Study on Information Technology Firms in Istanbul’s Science-Parks - Ogrenci, Seher; Alpkan, Lutfihak; Karacay, Gaye; Bulut, Cagri (World Scientific Pub Co Pte Ltd, 2023)
This study aims to explore the dynamic capabilities (DCs) framework (with sensing, seizing, and reconfiguration dimensions) by exploring the fulfilment layer and underlying processes and structures employed in business model innovation (BMI) process within both new and established entrepreneurial firms. We employed exploratory and descriptive qualitative research method and gathered data through semi-structured interviews with entrepreneurs of nine firms operating in the science-park settings in Istanbul, Türkiye. This study uncovered rich insights about the DCs, as categorized in this study under 10 sub-dimensions. In addition, three different fulfilment layers of DCs emerged at the entrepreneurial firms: (i) the entrepreneurial capabilities at the individual layer, (ii) the entrepreneurial team’s complementary capabilities at the top managerial layer, and (iii) the mechanisms and routines at the organizational layer. DC sub-dimensions suggested in our study are clues for entrepreneurs to develop BMIs. Practitioners are recommended to consider their primary responsibility for BMIs processes independent of the size of the firms, to build entrepreneurial teams with partners having the complementary skill set and concentrate on the employees’ selection, as well as their adaptation to the firm routines. Additionally, the study complements Teece’s theoretical DC framework on BMI extending it into fulfilment layer and opens a fruitful research area for scholars.